Characterization of PEGylated Niosomal Nanoparticles Loaded with Curcumin and their Effects on Human Ovarian Cancer Cells - Khomami, Zahra; Abbasi, Mahsa; Zonoubi, Niloofar; Sharafi-Badr, Paria; Ghasemzadeh, Shabnam; Khursandov, Ilyos (Asian Pacific Journal of Cancer Biology, 2025)
Overview: Curcumin is known for its broad range of biological properties, particularly its anticancer effects. However, its poor bioavailability limits its therapeutic potential at the tumor site. To overcome this limitation, this study aimed to develop a nanoniosomal formulation of curcumin using polyethylene glycol to improve its delivery and efficacy against ovarian cancer cells in vitro. Methods: Curcumin-loaded nanoniosomes were synthesized via the reverse-phase evaporation method. The resulting nanoparticles were characterized for their particle size, zeta potential, and drug release profile. Drug loading and encapsulation efficiency were also measured. For biological evaluation, the human ovarian cancer cell line A2780S was treated with the nanoniosomal formulation, and cytotoxicity was assessed using the MTT assay. Results: The prepared nanoniosomes had an average particle size of 222.3 ± 17.6 nm and a zeta potential of −28.4 ± 1.1 mV, indicating good colloidal stability. Drug loading and encapsulation efficiency were found to be 50.8 ± 7.3% and 24.3 ± 1.3%, respectively. The in vitro release study revealed a sustained release profile, with 50.1 ± 5.9% of curcumin released over 34 hours. MTT assay results demonstrated that the nanoniosomal curcumin exhibited significantly higher cytotoxicity compared to free curcumin against A2780S cells. Conclusion: The findings suggest that curcumin-loaded nanoniosomes represent an effective drug delivery system that enhances the bioavailability and anticancer activity of curcumin. This nanocarrier system shows promise as a chemopreventive strategy for the treatment of ovarian cancer and warrants further preclinical evaluation.